2015
DOI: 10.1590/0103-6440201300032
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Poly-L-Lactic Acid Scaffold's Pore Size on the Proliferation and Differentiation of Dental Pulp Stem Cells

Abstract: The aim of this study was to evaluate the influence of the poly-L-lactic acid (PLLA)-based scaffold's pore size on the proliferation and differentiation of dental pulp stem cells (DPSCs). The scaffolds were prepared in pulp chambers of 1-mm-thick tooth slices from third molars using salt crystals (150-250 µm or 251-450 µm) as porogen. DPSC (1x10 5 cells) were seeded in the scaffolds with different pore sizes, and cultured in 24-well plates. The cell proliferation was evaluated using the WST-1 assay after 3-21 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 24 publications
(47 reference statements)
2
16
0
Order By: Relevance
“…They demonstrated that scaffolds with pore size in the range of 150–300 μm supported more adhesion and proliferation of cells . Interestingly, Conde et al did not observed any difference in proliferation as well as odontogenic differentiation of DPSCs on PLLA scaffold with pore size range from 150 to 450 μm . A study by Choi et al has revealed that uniformity in pore size in PLGA scaffolds is in favor of both preosteoblasts even distribution and differentiation .…”
Section: Resultsmentioning
confidence: 99%
“…They demonstrated that scaffolds with pore size in the range of 150–300 μm supported more adhesion and proliferation of cells . Interestingly, Conde et al did not observed any difference in proliferation as well as odontogenic differentiation of DPSCs on PLLA scaffold with pore size range from 150 to 450 μm . A study by Choi et al has revealed that uniformity in pore size in PLGA scaffolds is in favor of both preosteoblasts even distribution and differentiation .…”
Section: Resultsmentioning
confidence: 99%
“…Conde, et al [35] developed a poly( l -lactic acid) scaffold using solvent-casting/particulate leaching to investigate the influence of pore size on the proliferation and differentiation of dental pulp stem cells. The scaffolds were prepared in pulp chambers of 1 mm thick tooth slices and porosity was developed using salt crystals of two sizes (150–250 µm or 251–450 µm) as porogen.…”
Section: Fabrication Of Synthetic Biopolymersmentioning
confidence: 99%
“…Vital pulp therapy based on the use of stem cell has promising research and therapeutic applications in dentistry. Stem cells in the dental pulp respond to tooth injuries by migrating, proliferating and differentiating into odontoblasts, which conduct the synthesis and secretion of tertiary dentin 6 , 9 , 17 , 32 . In particular, deciduous teeth contain a population of postnatal “stem cells from human exfoliated deciduous teeth” (SHED), which are capable of extensive proliferation and multipotential differentiation in vitro 8 , 17 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Following the diagnosis of deep carious/traumatic pulp injuries of primary and permanent teeth, vital pulp therapy may be clinically performed by applying a capping material directly onto the pulp tissue to allow pulp/dentine regeneration 2 , 12 . During conservative pulp treatments such as pulpotomy and direct pulp capping, interactions between pulp cells and the capping material affect stem cell proliferation 6 , 29 . While the exact nature of interactions between capping materials and the injured pulp tissue (during wound healing and regeneration) remains unclear, in vitro studies in two or three-dimensional culture systems as well as in vivo studies on capping materials have aided in material selection, which is the key to ensure a good treatment outcome 2 , 6 , 8 , 15 , 26 , 29 .…”
Section: Introductionmentioning
confidence: 99%